Participatory reading in late-medieval England - Blatt, Heather (Manchester medieval literature and culture., 2019)
This book traces affinities between digital and medieval media, exploring how reading functioned as a nexus for concerns about increasing literacy, audiences' agency, literary culture and media formats from the late fourteenth to the early sixteenth centuries. Drawing on a wide range of texts, from well-known poems of Chaucer and Lydgate to wall texts, banqueting poems and devotional works written by and for women, Participatory reading argues that making readers work offered writers ways to shape their reputations and the futures of their productions. At the same time, the interactive reading practices they promoted enabled audiences to contribute to -- and contest -- writers' burgeoning authority, making books and reading work for everyone.